2013
DOI: 10.1111/dsu.12112
|View full text |Cite
|
Sign up to set email alerts
|

All Monofilament Knots Assume Sliding Conformation In Vivo

Abstract: When monofilament suture is securely cinched in vivo, kinetic energy forces even a flat throw into sliding conformation. A well-crafted, intentionally sliding square knot appears compacter than any other monofilament knot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Rijkhenuizen et al [7] recommend using a monofilament material and a transfixing knot as the ligation method of choice in castration. However, recent studies on monofilament sutures have demonstrated that flat knots assume a sliding conformation when held under unequal tension [21]. This in turn generates stress on the suture, which breaks precisely at the point at which the configuration of the knot changes [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Rijkhenuizen et al [7] recommend using a monofilament material and a transfixing knot as the ligation method of choice in castration. However, recent studies on monofilament sutures have demonstrated that flat knots assume a sliding conformation when held under unequal tension [21]. This in turn generates stress on the suture, which breaks precisely at the point at which the configuration of the knot changes [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…With the monofilament suture material, the two different ligating methods produced similar results and were more resistant to pressure than the surgeon’s knot technique performed with multifilament suture material. This difference is likely due to the elastic properties of the monofilament suture that give more grip to the stretched portion within the knots as previously described[ 19 ]. Recent studies on several knot types using monofilament suture material demonstrated that under tension the square knot changes its conformation into a sliding knot [ 19 ].…”
Section: Discussionmentioning
confidence: 95%
“…This difference is likely due to the elastic properties of the monofilament suture that give more grip to the stretched portion within the knots as previously described[19]. Recent studies on several knot types using monofilament suture material demonstrated that under tension the square knot changes its conformation into a sliding knot [19]. This alteration generates stress on the thread that breaks precisely at the point where knot’s configuration mutates [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Hendrickson also reported that monofilament suture holds knots more securely than braided material. Flat knots created with monofilament suture assumed a sliding conformation when held under unequal tension in a recent study . This configuration change creates stress on the suture material, causing breakage within the knot .…”
Section: Discussionmentioning
confidence: 99%
“…Flat knots created with monofilament suture assumed a sliding conformation when held under unequal tension in a recent study . This configuration change creates stress on the suture material, causing breakage within the knot . Using a friction or sliding knot with monofilament suture avoids such a risk, thereby increasing security …”
Section: Discussionmentioning
confidence: 99%